EVALUASI PELAKSANAAN KEGIATAN PROMOTIF DI POS KESEHATAN DESA (POSKESDES) DI DESA SIAGA KECAMATAN RIMBO BUJANG KABUPATEN TEBO PROVINSI JAMB - , M.Ridwan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: One of criteria of an alert village is the availability of Poskesdes. Poskesdes activities can be carried out in a new building, the house of a midwife or village polyclinic (polindes). The function of Poskesdes associated with promotive activities is to encourage active role of the community as early alert against risks for various public health problems and as a foundation for networking of community based health efforts in the village. Objective: To identify the process of promotive activity implementation at Poskesdes Subdistrict of Rimbo Bujang District of Tebo Jambi. Method: The study used qualitative method. There were 16 informant consisting of 3 midwives, 6 Poskesdes cadres, 2 community leaders, 2 heads of village, 1 staff of health center, 1 staff of Tebo district health office, and 1 staff of Jambi provincial health office. Data were obtained from indepth interview, document study and observation at Poskesdes. Triangulation, member checking and debriefing were made to ensure data validity. Data analysis used theory Miles and Huberman (1992) method. Result: Promotive activities at Poskesdes were implemented in terms of preparation for alert village program by Jambi Provincial Health Office and Tebo District Health Office. The activities included encouragement for active role of the community by involving midwives in coordination with heads of villages, community leaders and cadres. Health centers took role in increasing capacity of cadres and supervising midwives of Poskesdes. Activities to improve alert for disease risk factors were implemented through surveillance that involved integrated service post (posyandu) and the utilization of religious activities. Poskesdes built network across sector through community organizations. Conclusion: Promotive activities at Poskesdes were influenced by active role of midwives, cadres, heads of villages, and community leaders. Community empowerment needed cooperation with community organizations and organizations that had similar objectives and worked across sector.